Ensaios de placas em solo laterítico na cidade de Santo Ângelo - Kublik, Cristiane (2010)
This thesis presents a study of the behavior of a soil profile typical of the Santo Ângelo city, the board is tested. This study aimed to investigate the behavior of natural soil, waterlogged, compacted and with addition of cement for their application in shallow foundations. The load tests were conducted in an area next to the building of the laboratories of the Civil Engineering Course, at Universidade Regional Integrada do Alto Uruguai e das Missões , URI, in Santo Ângelo. The geotechnical characterization tests were conducted in disturbed and undisturbed samples collected from trenches and pits during the test plate. Pedologicaly soil consists of a thick surface horizon (horizon A and B) classified as Typic. This texturally soils were classified as silty clays and silty clays, sandy, porous and unsaturated. In terms of resistance of these soils show a cohesion of 10 kPa and a friction angle of 32 degrees. These values are reduced as flooded, mainly in relation to cohesion. The flooding also reduces the strength parameters, causes a collapse that was assessed by means of direct shear tests and compression tests contained doubles. The collapse of values measured was between 1% and 3%. The effect of flooding there was also confined compression tests, with the stress reduction of pre-densification and increased compressibility. In plate tests verified the influence of flooding on the deformability and strength of these soils. Flooding increased deformability and reduced the resistance, but it was found that a natural rain prior to testing in natural soil was more effective than a process of artificial flooding. For tests on compacted soil and soil-cement had decreased deformability and increased resistance of these soils. This increased rigidity and resistance was more intense in the soil-cement. Therefore, the use of compression techniques and the addition of cement increases the load capacity of soils for use in shallow foundations.